UJI EFEKTIVITAS SARI BUAH KURMA (Phoenix dactylifera) TERHADAP GAMBARAN HISTOPATOLOGI GASTERMENCIT JANTAN (Mus musculus L) YANG DIBERI ASPIRIN - BUNGA PUTRI AYUNIRRAHIM; YENITA YENITA (LP2MTBM MAKARIOZ, 2023)
Date palm juice (Phoenix dactylifera) isProcessed products from dates, which have various contents that are beneficial for health. Research has been carried out to test the effectiveness of date palm juicewhich aims to determine the effectiveness of date palm juice on the gastric histopathological picture of male mice (Mus musculus L) given aspirin. Method:This research is an experimental study with a research design of